2018
DOI: 10.1186/s12890-018-0703-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival after repeated surgery for lung cancer with idiopathic pulmonary fibrosis: a retrospective study

Abstract: BackgroundPatients with idiopathic pulmonary fibrosis (IPF) have a high risk of developing lung cancer, but few studies have investigated the long-term outcomes of repeated surgery in such patients. The purpose of this study was to evaluate the surgical outcomes of repeated lung cancer surgery in patients with IPF.MethodsFrom January 2001 to December 2015, 108 lung cancer patients with IPF underwent pulmonary resection at two institutions; 13 of these patients underwent repeated surgery for lung cancer, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Previous studies have indicated that patients with IPF are at high risk for lung cancer [10,31,32], and the survival of patients with IPF is clearly related to the development of lung cancer [33,34]. The association between IPF and lung cancer also has been demonstrated by the clinicopathological and imaging characteristics of lung cancer associated with IPF [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that patients with IPF are at high risk for lung cancer [10,31,32], and the survival of patients with IPF is clearly related to the development of lung cancer [33,34]. The association between IPF and lung cancer also has been demonstrated by the clinicopathological and imaging characteristics of lung cancer associated with IPF [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The annual incidence of AE in patients with IPF has been reported as 5–15% [26]. Additionally, the incidence rate of AE triggered by chemotherapy [27], surgery [28], and radiotherapy [29] is increased in patients with IPF. In our study, the total incidence of AE was 15.7%.…”
Section: Discussionmentioning
confidence: 99%
“…AE-IPF always occurs spontaneously without verifiable causes. The incidence of postoperative AE-IPF was reported to be fairly high in patients with lung cancer, ranging from 9% to 24% (4,7,8). Potential etiologic factors included, at the least, but are not limited to the following: preoperative disease hyperactivity, high concentrations of oxygen during the operation, mechanical ventilation, intraoperative mechanical-ventilation-related lung injury, and postoperative reduction of the glucocorticoid dose and other drugs (9).…”
Section: Discussionmentioning
confidence: 99%